2010
DOI: 10.1097/ta.0b013e3181b16e3d
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Bone Grafting in Tibial Plateau Fracture Fixation

Abstract: CMBG using fresh-frozen allograft in depressed tibial plateau fractures provides structural support sufficient to maintain the height of the tibial plateau, is associated with few complications in complex patients with large bone loss, and has theoretical advantages of graft incorporation and remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Other studies have suggested that IBG was able to provide the stability required in segmental bone defects to sustain unrestricted weight-bearing [42] and was a technique to augment ORIF in nonosteoporotic TPFs [19,20]. One study reported that three patients with TPFs treated with IBG mobilised weight-bearing as tolerated postoperatively and regained full weight-bearing within 6 weeks without loss of fracture reduction as measured by RSA [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested that IBG was able to provide the stability required in segmental bone defects to sustain unrestricted weight-bearing [42] and was a technique to augment ORIF in nonosteoporotic TPFs [19,20]. One study reported that three patients with TPFs treated with IBG mobilised weight-bearing as tolerated postoperatively and regained full weight-bearing within 6 weeks without loss of fracture reduction as measured by RSA [19].…”
Section: Discussionmentioning
confidence: 99%
“…Unsatisfactory results and a progressive increase in the prevalence of these fractures led us to look for alternative treatment options. Impaction bone grafting (IBG) has previously been used to reconstruct bone stock at revision hip replacement surgery [17,18] and shown to be a feasible option to augment ORIF of TPF [19,20] in non-osteoporotic patients. Therefore IBG was seen as a reconstruction technique that could potentially augment ORIF of osteoporotic TPFs by improving screw purchase, preventing loss of fixation, and providing the stability required to allow early weightbearing.…”
Section: Introductionmentioning
confidence: 99%
“…7-10 Cancellous autograft was long considered the standard of care for the management of these subchondral bone voids, 11,12 and relatively good results were reported with its use. 7,8 However, after the development of injectable calcium phosphate cement, surgeons almost immediately realized the possible benefits of this bone graft substitute with regard to tibial plateau fractures. Lobenhoffer et al 10 published the first substantial case series using this product in 26 tibial plateau fractures and reported promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of articular subsidence reported in clinical studies using cancellous bone graft range anywhere between 12.5% and 61.5%. 1,7,17 Calcium phosphate cement seems to offer improved performance, with subsidence rates reported between 7.8% and 23%. 1,10,17 The most scientifically robust study in this area was performed by Russell and Leighton; this was a randomized control trial comparing autogenous iliac crest bone graft with calcium phosphate cement.…”
Section: Discussionmentioning
confidence: 99%
“…Large bone defects caused by trauma or tumor resection often result in long lasting morbidity due to their limited healing capacity. Standard treatment options consist of the use of autologous or allogenic bone grafts, or distraction osteogenesis 1, 2. The clinical outcome of these treatment modalities often seems satisfactory, although they have major drawbacks such as donor site morbidity and/or host versus graft disease, as well as long healing times 3–5.…”
Section: Introductionmentioning
confidence: 99%